Rethinking Housing Bubbles : The Role of Household and Bank Balance Sheets in Modeling Economic Cycles - Gjerstad, Steven D.; Smith, Vernon L. (Cambridge : Cambridge University Press, 2014)
In this highly original piece of work, Steven D. Gjerstad and Nobel Laureate Vernon L. Smith analyze the role of housing and its associated mortgage financing as a key element of economic cycles. The authors combine data from both laboratory and real markets to provide insight into the bubble propensity of real-world economic actors and use novel historical analysis on the Great Recession, the Great Depression, and all of the post-World War II recessions to establish the critical roles of housing, private-capital investment, and household and private institutional balance sheets in economic cycles. They develop a model that incorporates household balance sheets and bank balance sheets and offers insights based on this analysis concerning policy going forward, effectively changing the way economists think about economic cycles.
Title from publisher's bibliographic system (viewed on 08 Oct 2015).
Keywords: Global Financial Crisis, 2008-2009